Employing the dimensions of e-government to achieve the requirements of honest organizations Academic analytical study - Hamd Kareem Al-Hdrawy; Aradn Hatem Al-Obaidy; Hamida Kareem Shaalan (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
This study sought to identify the important topic of in the shadow of current conditions and internal and external environment, which needs urgent reform to achieve social aims, and we take e- government and its dimension as a strategic approach , and apply it in random sample of university professors , it has built and test strategic model according to the relationship of the variables ,the study has conclude thtt e-leadership, technological infrastructure and human efficiency are positively reflected on the achievement of honest organizations.